The BASES expert statement on genetic research and testing in sport and exercise science - Williams, A.; Miah, A.; Harris, R.; Montgomery, H.; Wackerhage, H. (The Sport and Exercise Scientist, 2012)
The future of sport and exercise science will become increasingly focused on genetic research and testing as the relevant molecular technologies become faster, cheaper and more widely available (Lander, 2011). Sport and exercise scientists need to ensure that they keep abreast with genomic science to capitalise on recent and anticipated findings in an ethically acceptable manner. It is recommended that: • Sport and exercise scientists should maintain their awareness of potential unwanted consequences of genetic information and of the potential misuse of genetic data to justify discriminatory views or practices. Sport and exercise scientists should engage knowledgeably in public debates to minimise those risks. • Genetic testing in the sport and exercise context (with the possible exception of pre-participation risk screening) should only be conducted on mature individuals who fully understand the relevant issues and a system of counselling should be introduced. • Pre-participation risk screening should not be obligatory and the confidentiality of such testing has to be ensured. • Sport and exercise scientists should be aware of the risk that a prominent "individualised medicine" public narrative could undermine the more general advice given to large population groups regarding the value of exercise and other lifestyle factors in disease prevention and treatment. • Genetic testing should be used in the fight against doping in sport where appropriate, to link biological samples to athletes, test claims that a genetic mutation was responsible for a positive doping test or unusual biochemical data, and test for gene doping.